2009
DOI: 10.1016/j.appdev.2008.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Parent cultural adaptation and child functioning in culturally diverse, urban families of preschoolers

Abstract: Parent cultural adaptation and preschool behavioral and socioemotional functioning were examined in a community sample of urban families from diverse cultural backgrounds. Participants were 130 families of children (mean age = 4.1 years) attending eight public Pre-Kindergarten programs in urban communities. Parents completed a measure of cultural adaptation that taps into acculturation and enculturation, and teachers reported on children’s externalizing problems, internalizing problems and adaptive behavior in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 31 publications
1
39
0
3
Order By: Relevance
“…For example, while some research fails to find a relation between parental acculturation and youth externalizing problems (e.g., Knight et al, 1994; Vega, Khoury, Zimmerman, Gil, & Warheit, 1995), other studies suggest that greater orientation to culture of origin is associated with more externalizing problems in Latino youth (e.g., Weiss et al, 1999). In contrast, some studies have found that greater orientation to U.S. mainstream culture is associated with more externalizing problems in Latino youth (e.g., Calzada, Brotman, Huang, Bat-Chava, & Kingston, 2009). Similarly, although research has linked parental acculturation to internalizing problems in youth, the nature of this relation is unclear (Dumka et al, 1997; Knight et al, 1994).…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…For example, while some research fails to find a relation between parental acculturation and youth externalizing problems (e.g., Knight et al, 1994; Vega, Khoury, Zimmerman, Gil, & Warheit, 1995), other studies suggest that greater orientation to culture of origin is associated with more externalizing problems in Latino youth (e.g., Weiss et al, 1999). In contrast, some studies have found that greater orientation to U.S. mainstream culture is associated with more externalizing problems in Latino youth (e.g., Calzada, Brotman, Huang, Bat-Chava, & Kingston, 2009). Similarly, although research has linked parental acculturation to internalizing problems in youth, the nature of this relation is unclear (Dumka et al, 1997; Knight et al, 1994).…”
Section: Introductionmentioning
confidence: 91%
“…Similarly, although research has linked parental acculturation to internalizing problems in youth, the nature of this relation is unclear (Dumka et al, 1997; Knight et al, 1994). While some studies have found that greater parental orientation to the Latino culture is associated with fewer internalizing in Latino youth (e.g., Calzada et al, 2009), other studies have produced conflicting findings (e.g., Gudiño & Lau, 2010). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Einen vergleichbaren Alterseffekt konnten Manassis et al (2007) (Dummit et al, 1997;Ford et al, 1998;Steinhausen & Juzi, 1996) und sechs mehrsprachig (S8, S13, S14, S15, S17 und S18). Die einsprachigen Kinder erfüllten (Calzada et al, 2009) und höheren sozialen (Pawliuk et al, 1996) sowie sprachlichen Kompetenzen (Oades-Sese & Li, 2011) einher.…”
Section: Vorhersage Der Entwicklung Des Sprechverhaltensunclassified